Dynamic Adaptive Environmental Flows (DAE‐Flows) to Reconcile Long‐Term Ecosystem Demands With Hydropower Objectives - Dalcin, Ana Paula; Marques, Guilherme Fernandes; Tilmant, Amaury; Olivares, Marcelo (Water resources research, 2023)
This study investigates how environmental flows (e‐flows) can be designed as dynamic operating policies to optimize long‐term economic and ecosystem performance in reservoir systems. The main goal is to provide e‐flow solutions that contribute to better preparedness and flexibility of hydro‐systems to face multiyear stress periods, reducing the impact of water crises. The methodology framework combines a fish‐flow model with a multi‐objective evolutionary algorithm to construct multiple environmental water demand curves and capture the opportunity cost of different levels of ecosystem preservation. The water demand curves applied to a stochastic dynamic hydro‐economic model then derive dynamic e‐flow policies that balance immediate and future water use tradeoffs. The approach, termed dynamically adaptive environmental flows (DAE‐flows), is demonstrated on the Paraná River Basin, Brazil, a large‐scale hydropower system. Results show that the approach can adjust e‐flows (coordinated with other hydro‐system releases) over the time horizon, sacrificing them at certain times at the expense of some ecosystem loss, but improving long‐term ecosystem functioning. A long‐term approach to adaptation also yields better results for the environment without imposing a hard constraint to hydropower during droughts. Even under a drier climate change scenario, this allowed maintenance and improvement of environmental performance in most years, so during severe droughts the water could still be reallocated to hydropower but at a lesser cost to the environment. Plain Language Summary The environment provides us with important resources (e.g., clean water, fish, livelihood and recreation). However, in order to thrive, the environment also needs water, which has specific patterns of flow in time depending on the species that live in the rivers and lakes. As we divert and store water in reservoirs to meet other important economic demands (e.g., hydropower) those flow patterns are disturbed, along with the species relying on it. This paper investigates how we can better represent flow patterns necessary to sustain fish life in large river systems, so we can identify and implement new strategies to achieve those flows downstream of reservoirs while still maintaining good performance to other economic demands. Results show that those strategies can not only be created by combining different patterns of flow but can also be updated and adjusted as conditions in the river change in the future, resulting from drought events and even different climates. To implement those strategies however, we need operations that are flexible and aimed at the future, besides the present. This is a key learning that helps us find better ways to adapt to future challenges, preserving our environmental assets while also meeting other important demands. Key Points Ecological‐flow relationships, hydrological conditions and long‐term ecosystem performance are applied as drivers of dynamic e‐flows Dynamic e‐flows conserve water in some periods at the expense of some environment loss to improve long‐term ecosystem functioning The operation of hydro‐systems can be adapted to reconcile long‐term economic and environmental demands